2021
DOI: 10.1186/s13049-021-00843-z
|View full text |Cite
|
Sign up to set email alerts
|

A pre-hospital risk score predicts critical illness in non-trauma patients transported by ambulance to a Dutch tertiary referral hospital

Abstract: Background Early pre-hospital identification of critically ill patients reduces morbidity and mortality. To identify critically ill non-traumatic and non-cardiac arrest patients, a pre-hospital risk stratification tool was previously developed in the United States. The aim of this study was to investigate the accuracy of this tool in a Dutch Emergency Department. Methods This retrospective study included all patients of 18 years and older transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This higher occurrence might be explained by the selection of the most severe and ill patients in our level one trauma center. The occurrence of critical illness as stated in this study is in concordance with a study done by the same study group in 2017 (10).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This higher occurrence might be explained by the selection of the most severe and ill patients in our level one trauma center. The occurrence of critical illness as stated in this study is in concordance with a study done by the same study group in 2017 (10).…”
Section: Discussionsupporting
confidence: 93%
“…Our primary hypothesis was that the specificity of medical caregivers would be significantly higher (20%), whereas sensitivity would be noninferior compared with MEWS greater than or equal to 3. Prior research in our centers reported an occurrence of critical illness in around 15% of all patients brought to the ED by EMS (10). Based on these findings, a loss to follow-up of 10%, alpha of 0.05, and a power of 80%, 193 medical judgments were needed to answer our primary outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to achieve earlier identification of the clinically deteriorating patient led to the introduction of Early Warning Scores (EWS) risk-stratification models 10 11. EWS are used to recognise the early signs of clinical deterioration by assessing various physiological variables (eg, BP, HR, oxygen saturation, RR, level of consciousness and temperature).…”
Section: Introductionmentioning
confidence: 99%
“…Time-sensitive disease groups were defined as those with out-of-hospital cardiac arrest, ACS, or acute stroke. We also tried to classify the critical cases, but that was difficult based on a prehospital evaluation [27]. We, therefore, used SI and mental change as indicators for ill patients.…”
Section: Discussionmentioning
confidence: 99%